The French pension system: A long-term macroeconomic perspective - Concialdi, Pierre (Pesquisa & Debate Revista do Programa de Estudos Pós-Graduados em Economia Política, 2023)
The article provides a long-term macroeconomic perspective of the French pension system since the early 20th century. It starts by reviewing the main stages in the construction of the French pension system and identifying the main characteristics of this system as it stands now. Turning to official projections, it shows that the generosity of the pension system should dramatically decline as a consequence of past reforms. The article then follows by discussing three key issues that dominate the public debate on pensions: the economic impact of demographic changes, the financing of pension benefits, and the relation between retirement, employment and work. The discussion shows that the financing of pensions should not create an impossible burden for the economy, thus mainly highlighting the political dimension of the choices to be made to adapt the pension system to future demographic and economic changes.